2012
DOI: 10.1128/jb.06827-11
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of the Synthesis of the MobM Relaxase Encoded by the Promiscuous Plasmid pMV158

Abstract: bThe streptococcal promiscuous plasmid pMV158 (5,540 bp) replicates by the rolling-circle mechanism and can be mobilized among a wide number of Gram-positive and -negative bacteria. The plasmid region involved in its conjugative transfer includes the mobM gene, which encodes the MobM relaxase, and the cis-acting origin of transfer (oriT). MobM initiates transfer by cleavage of supercoiled pMV158 DNA at a specific dinucleotide within oriT. In the present work, we have performed a detailed transcriptional analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 52 publications
1
28
0
1
Order By: Relevance
“…3), the generation of cruciform secondary structures by one of them would hinder the formation of the other, indicating that the target DNA accessibility by the relaxase could depend on the plasmid DNA superhelicity (Fernández-López et al, 2014). Our in vitro analysis demonstrated that MobM binds specifically to ssDNA encompassing IR1/3 with high affinity (Lorenzo-Díaz et al, 2011), which allowed the MobM protein to repress its own synthesis (Lorenzo-Díaz et al, 2012). Functional relevance of the IRs in the different steps of the conjugative process is currently under exploration.…”
Section: The Mob V Familymentioning
confidence: 81%
“…3), the generation of cruciform secondary structures by one of them would hinder the formation of the other, indicating that the target DNA accessibility by the relaxase could depend on the plasmid DNA superhelicity (Fernández-López et al, 2014). Our in vitro analysis demonstrated that MobM binds specifically to ssDNA encompassing IR1/3 with high affinity (Lorenzo-Díaz et al, 2011), which allowed the MobM protein to repress its own synthesis (Lorenzo-Díaz et al, 2012). Functional relevance of the IRs in the different steps of the conjugative process is currently under exploration.…”
Section: The Mob V Familymentioning
confidence: 81%
“…We have shown that MobM is able to negatively regulate the transcription of its own gene (76). This does not seem to be the case of several other plasmids, which require an accessory protein for transcriptional regulation of the relaxase synthesis (77).…”
Section: Plasmid Pmv158mentioning
confidence: 99%
“…Two promoters placed nearly in tandem, and termed P mob1 and P mob2 , are used by the host RNAP: the latter is preferentially used in E. coli (76), whereas the former is used in L. lactis (51). Whereas promoter P mob1 was mapped to reside within oriT pMV158 , promoter P mob2 was found to be adjacent to it; and yet both promoters were subjected to self-regulation by MobM in E. coli (76). Given the relative positions of RNAP and MobM proteins in the region encompassing the two promoters (Fig.…”
Section: Plasmid Pmv158mentioning
confidence: 99%
See 2 more Smart Citations